2000
DOI: 10.1124/mol.58.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Metabolism-Dependent and -Independent Neutrophil Apoptosis by Clozapine

Abstract: Clozapine, an atypical antipsychotic used in the treatment of refractory schizophrenia, causes neutropenia and agranulocytosis in 3 and 0.8% of patients, respectively. Clozapine undergoes bioactivation to a chemically reactive nitrenium ion, which has been shown to cause neutrophil cytotoxicity. To define further the mechanism of cell death, we have investigated the toxicity of clozapine, its stable metabolites, and its chemically reactive nitrenium ion to neutrophils and lymphocytes. Clozapine was able to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 38 publications
3
84
0
5
Order By: Relevance
“…First-strand cDNA reactions for each cell type primed with either oligo(dT) [12][13][14][15][16][17][18] or random hexamers, essentially gave similar results with cDNA species of up to 8 kb synthesized (data not shown). Subsequent amplifications of cDNA prepared using either priming method gave identical results for each receptor targeted (Figure 1a-d).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…First-strand cDNA reactions for each cell type primed with either oligo(dT) [12][13][14][15][16][17][18] or random hexamers, essentially gave similar results with cDNA species of up to 8 kb synthesized (data not shown). Subsequent amplifications of cDNA prepared using either priming method gave identical results for each receptor targeted (Figure 1a-d).…”
Section: Resultsmentioning
confidence: 74%
“…The integrity of the RNA isolated was assessed [12][13][14][15][16][17][18] and random hexamers. To increase the sensitivity of PCR amplification of cDNA targets, the RNA template was removed by digestion with 2.0 U RNase H after completion of first-strand synthesis.…”
Section: Rna Extraction and First Strand Cdna Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the metabolite can potentially be metabolized back to clozapine [21] which may in part explain the variability in profiles of primary stromal and HAS303 cell viability across clozapine N-oxide concentrations. Studies with the neutrophil have also shown no concentration dependent induction of cell death in the presence of up to 300 µM clozapine Noxide [22] . It is noteworthy that LP101 cells in the presence of clozapine and its metabolites showed limited fluctuations in viability across drug concentrations, compared with that seen with primary stromal and HAS303 cells.…”
Section: Resultsmentioning
confidence: 99%
“…2 The mechanism of clozapine-induced agranulocytosis is not fully explained; however, it has been postulated as immunemediated mechanism and direct toxic effects. 3,4 It has been demonstrated that the reactive nitrenium ion, a toxic metabolite, is produced from clozapine through myeloperoxidase-H 2 O 2 -dependent reaction, and then induces the apoptosis of neutrophils in vitro. 4 In order to determine whether clozapine-treated bone marrow cells were susceptible to cell death, we compared the expression profiles of bone marrow cells between clozapine-and vehicle (saline)-treated mice using cDNA microarray analysis.…”
mentioning
confidence: 99%